MENERAPKAN PEMBELAJARAN AKTIF UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR EKONOMI PESERTA DIDIK - Dewi Koryati; Dian Eka Amrina; Siti Fatimah; Dewi Pratita (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
To discuss conceptual economic materials, active learning techniques are very well used. How, by combining three methods of teaching (triple methods), namely; Simulation, discussion, and cooperative learning.This technique can also improve the motivation and outcome of economic learning, because learners play a direct role in learning and training their skills to solve economic problems. The research uses the one group pretest-posttest design. Data obtained through pretests and posttest and a questionnaire against 33 respondents in the class XI.2 Social Science, High School. Hypothesized test with the parametric test-T sample statically correlates. Analysis results showed significant increases in learning outcomes after active learning. Students' understanding of the command economic system, the concept of the market, and the concept of opportunity cost with good value. Understanding the main problems of economic sciences, concepts and basic principles of productive efficiency, concepts and principles of the market economic system, and the concept of cost of opportunities for the most skilled workforce. The learners ' ability to analyse the fundamental economic objectives of the Community and its relationship with the economy policy is less value. The rate of motivation to study economics increased by 1.57%, but there was no significant increase in motivation after they had participated in active learning